A randomized, open, controlled trial of tretinoin 0.05% cream vs. low-dose oral isotretinoin for the treatment of field cancerization - Ianhez, Mayra; Pinto, Sebastião A.; Miot, Helio A. [UNESP]; Bagatin, Ediléia (Wiley, 2019)
Background: Sun exposure may lead to actinic keratoses (AKs), field cancerization, and skin cancer. Effective treatment of AKs and field cancerization is important. Oral and topical retinoids can be used for this purpose. To compare clinical, histological, and immunohistochemical effects of oral and topical retinoid for AKs and field cancerization on face and upper limbs of immunocompetent patients, as well as the impact on quality of life, safety, and tolerability. Methods: This study compared 10 mg/day oral isotretinoin (ISO) to 0.05% tretinoin cream (TRE) every other night, associated with sunscreen (SPF 60). Patients of both genders, aged 50–75 years, underwent cryotherapy with liquid nitrogen for AKs at baseline and after 120 days when they were randomized into two groups, TRE (n = 31) and ISO (n = 30), for 6 months. Outcome measures were: number of AKs, histological (thickness of stratum corneum and epithelium) and immunohistochemical parameters (p53, Bcl-2 and Bax), dermatology life quality index (DLQI), and adverse events. Results: Both treatments reduced the number of AKs (around 28%), the thickness of stratum corneum, and expression of p53 and Bax. By contrast, the epithelium thickness and Bcl-2 expression increased. There was no difference in the outcomes between TRE and ISO. Both treatments improved quality of life and were well tolerated with minimal side effects. Conclusions: Retinoids are effective and safe for field cancerization. Classical treatments for field cancerization (imiquimod and ingenol mebutate) are used for a short period; retinoids may be a good choice to intercalate with them and can be used continuously.